Fundamentos jurídicos para establecer la correcta aplicación del segundo párrafo del artículo 240° del código procesal civil Perú 2022 - Flores Cordova, Cei Gilmar (2024)
The role of the Judiciary (PJ) in administering justice in the country is pivotal, particularly through its jurisdictional bodies led by magistrates. These justice operators play a crucial role in adjudicating claims and assessing the admissibility of evidence presented by the parties. This study focuses on the issue stemming from the improper application of Article 240 of the Peruvian Civil Procedural Code by magistrates, specifically in the evaluation of claims that present expired judicial records as evidence. The research reveals that many judges improperly restrict the admission of these records to only one type of document (judicial resolutions), contradicting the article which permits the verification of the existence of an expired record with various types of documents. The main objective was to establish legal foundations for the correct application of the aforementioned article in judicial proceedings, ensuring adherence to fundamental principles such as human dignity, procedural expediency, effective judicial protection, due process, and document continuity. The methodology employed was exploratory qualitative research using the function-action design to generate new insights and key principles guiding judicial administration.